Out of the crisis: an empirical investigation of place-specific determinants of economic resilience. Issue 2 (1st February 2017) - Sedita, Silvia Rita; De Noni, Ivan; Pilotti, Luciano
ABSTRACT: This article attempts to isolate the structural characteristics that affect the resilience of a regional economy. It focuses on the role played by related/unrelated variety and differentiated knowledge bases as drivers for regional resilience and originally explores their interdependences. Italy is the empirical setting, and Italian local labour systems the unit of analysis. Regional resilience is measured as growth of the employment rate after the Great Recession that began in 2008. Results confirm the importance of related variety and of differentiated knowledge bases as drivers for regional resilience. We found support of the creative capacity of culture argument, providing evidence that a moderate concentration in symbolic knowledge-based economic activities contributes to resilience. Synthetic and analytical knowledge-based activities provide positive and no support to regional resilience, respectively. Finally, the relatedness of the symbolic knowledge-based activities increases regional economic resilience. Some policy implications are then derived from these findings.